Geopolitics : the geography of international relations - Cohen, Saul B. (Saul Bernard), 1925-2021.; Cohen, Saul B. (Saul Bernard), 1925-2021. (Lanham, Md. : Rowman & Littlefield, 2009)
Examines the dramatic changes wrought by ideological and economic forces unleashed by the end of the Cold War. Saul Cohen considers these forces in the context of their human and physical settings and explores their geographical influence on foreign policy and international relations.
Introduction -- Survey of geopolitics -- Geopolitical structure and theory -- The Cold War and its aftermath -- North and Middle America -- South America -- Maritime Europe and the Maghreb -- Russia and the Eurasian convergence zone -- The East Asia geostrategic realm -- The Asia-Pacific rim -- South Asia -- The Middle East shatterbelt -- Sub-Saharan African shatterbelt -- Epilogue.
Originally published under the title: Geopolitics of the world system.
Includes bibliographical references (pages 429-435) and index.
Keywords: Geopolitics; World politics; Ethnic relations; Security, International; International relations; Low-intensity conflicts (Military science); Relations interethniques; international relations; Ethnic relations; Geopolitics; International relations; Low-intensity conflicts (Military science); Security, International; World politics; Geopolitik